1970
DOI: 10.3126/sw.v5i5.2654
|View full text |Cite
|
Sign up to set email alerts
|

Breeding Performance and Nursery Practices of <i>Labeo Bata</i> (Hamilton-Buchanan, 1822)

Abstract: Abstract:A study was conducted to observe the breeding performance and nursery practices of the threatened indigenous fish species Labeo bata in Jessore (Longitude: 89 o 122 003 East; Latitude: 23 o 102 453 North), Bangladesh during 1998 to 2002. Eight trial doses of PG (Pituitary Gland) used for induced breeding of L. bata were 1.0mgPG/kg in the first dose, and 1.0 to 8.0mgPG/kg in second dose for female. On the other hand, five trial doses were administered for the male to identify the suitable single dose (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 4 publications
2
5
0
Order By: Relevance
“…However, Prasad (2009) reported higher relative fecundity of L. dero with wild brooders. The fertilization rate of 90±2.5% and hatching rate of 78±4.5% was recorded in present study, which is comparable with L. dyocheilus (Sarkar et al, Pandey et al, 2011) and L. bata (Hossain et al, 2007).…”
Section: Resultssupporting
confidence: 77%
“…However, Prasad (2009) reported higher relative fecundity of L. dero with wild brooders. The fertilization rate of 90±2.5% and hatching rate of 78±4.5% was recorded in present study, which is comparable with L. dyocheilus (Sarkar et al, Pandey et al, 2011) and L. bata (Hossain et al, 2007).…”
Section: Resultssupporting
confidence: 77%
“…The water temperatures recorded during the study period in both experiments were within the suitable range for fish culture (DOF, 2010). Hossain et al, (2007) also reported similar temperature ranges during nursery practices of L. bata. But, the ranges of pH were 7 in T 1 , T 2 , T 3 and nursery rearing pond respectively.…”
Section: Resultssupporting
confidence: 52%
“…Similarly, in our study we obtained the highest length, weight and survivability when L. bata fry were fed with mixed diet (50% wheat bran + 50% maize bran) for 60 days. In an another study (Selvaraj et al, 1972), L. boggut spawn were fed with zooplanktonic food for 10 days and the total length was obtained 16.993mm which was almost similar when rice bran was used (Hossain et al, 2007). This suggests that the growth and survival rate of carp hatchlings depend largely on the easy availability of planktonic food organisms in general.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations